TNF-induced metalloproteinase-9 production is associated with neurological manifestations in HTLV-1-infected individuals - Guerra, Mariele; Carvalho, Natália B.; Santos, Silvane; Nascimento, Mauricio T.; Sá, Renata; Carvalho, Augusto M.; Carvalho, Edgar M.; Carvalho, Lucas P. (Frontiers in Immunology, 2022)
HTLV-1-infected individuals may develop a neurologic inflammatory condition known as HTLV-1-associated myelopathy (HAM/TSP), in which the high production of TNF is observed. These patients exhibit higher proviral loads, enhanced production of proinflammatory cytokines and lymphocyte proliferation in comparison to asymptomatic HTLV-1 carriers and those presenting overactive bladder (OAB-HTLV-infected). Metalloproteinases (MMPs) are known to degrade the components of the blood-brain barrier, favoring the migration of infected cells into the central nervous system. Moreover, the unbalanced production of MMPs and their inhibitors (TIMPs) has also been associated with tissue damage. The present work studied the production of MMP-9 and TIMPs in HTLV-1-infected individuals with and without neurological manifestations. HAM/TSP patients presented higher concentrations of MMP-9 in peripheral blood mononuclear cell (PBMC) culture supernatants, as well as a higher MMP-9/TIMP-3 ratio when compared to the other groups studied. MMP-9 levels positively correlated with proviral load and TNF in OAB-HTLV-infected individuals, and the in vitro neutralization of TNF significantly decreased MMP-9 levels in PBMC culture supernatants. Our findings indicate an association between MMP-9 production and the proinflammatory state associated with HTLV-1 infection, as well as HAM/TSP.